2008
DOI: 10.1007/s15010-008-8125-9
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of COPD Patients Infected with Multi-Resistant Pseudomonas aeruginosa: A Case and Control Study

Abstract: In COPD patients admitted to the general ward, acute exacerbation with MDRP in sputum was associated with higher mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 29 publications
3
37
0
Order By: Relevance
“…Previously, only a case-control study had reported similar results, but it was limited to patients hospitalized with multiresistant PA. Moreover, in that study, patients with susceptible PA accounted for 20% of the controls [9]. Another more recent prospective publication performed in 116 ambulatory patients with severe disease obtained similar results.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Previously, only a case-control study had reported similar results, but it was limited to patients hospitalized with multiresistant PA. Moreover, in that study, patients with susceptible PA accounted for 20% of the controls [9]. Another more recent prospective publication performed in 116 ambulatory patients with severe disease obtained similar results.…”
Section: Discussionsupporting
confidence: 57%
“…Nevertheless, there is a lack of information regarding the relation between PA isolation and subsequent mortality. To our knowledge, only one previous case-control study has shown a higher mortality after hospitalization for COPD in patients with multiresistant PA [9]. …”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is strengthened by the study of Loureiro et al (2002), which demonstrated that prior antibiotic use was associated with bloodstream infections in the NICU. Recently, a case-control study showed that multi-drug resistant (MDR) P. aeruginosa caused significantly higher mortality rates among patients with chronic obstructive pulmonary disease than did infection with non-MDR strains (Montero et al, 2009). MDR strains are also of particular concern in vulnerable infants, such as those being treated in the NICU; Crivaro et al (2009) reported that both deaths associated with P. aeruginosa infections in the NICU outbreak reviewed here were associated with MDR isolates of P. aeruginosa.…”
Section: Biofilm Formation and Antibiotic Resistancementioning
confidence: 83%
“…An important clinical concern related to PA is its acquisition of resistance to one or more antimicrobial agents [14,37]. We previously demonstrated that hospitalized COPD patients had a high incidence of PAR, which was associated with PA persistence in the sputum after antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%